Crenças de autoeficácia do professor coordenador pedagógico: relevância para formação continuada - VIEIRA, Andréia Maria de Souza (2016)
This work is structured in three studies, the research and analysis of perceived self-efficacy beliefs of Educational Coordinator in his role in the continuing education of teachers in the school. The first study aims at presenting a literature review on Professor Educational Coordinator from 2000 to 2014, from the collection of empirical work on database. Publications material included three thematic involving Professor Educational Coordinator: role assignments; identity and aspects of affective and relational dimensions, which made it possible to show that the continuing education of teachers in school consists of mediation Educational Coordinator, in order to develop a consistent practice for improving student learning. It also pointed to the deviation of the pedagogical function that is still marked bureaucratic precepts. In the second study shows the Social Cognitive Theory of Albert Bandura in order to explain the basic concepts of this theoretical perspective, in particular, the Self-efficacy. The theme of self-efficacy in educational context was discussed at different levels of education: elementary school, high school and higher education. The results showed the meditational role that self-efficacy beliefs have on human behavior and training. The third study aimed to investigate and analyze the self-efficacy beliefs perceived by Professor Educational Coordinator in his role in the continuing education of teachers in the school. The participants were ten teachers working in function called Educational Coordinator in the state public schools of the “Diretoria de Ensino da Região de Assis”. The instrument used for data collection was the semi structured interview guide on the beliefs of teacher self-efficacy. From the data analysis it was observed that the self-efficacy perceptions of the participating subjects are consistent with the theoretical framework of Albert Bandura, addressed within the educational context. The four sources of formation of self-efficacy beliefs were perceived by Teachers Coordinators. Social persuasion stood out in speeches, both to the constitution of one's beliefs, and for the formation of this belief in the teacher, as emphasized dialogue and feedback on their actions. It is hoped that the study glimpse possibilities to think of continuing education proposals for strengthening the belief of personal and collective self-efficacy of those involved in the promotion of quality education.